First report of nematode parasites of Physalaemus albonotatus (Steindachner, 1864) (Anura: Leiuperidae) from Corrientes, Argentina - Gonzalez, Cynthya Elizabeth (2012)
Thirty-four adults of Physalaemus albonotatus(20 males and 14 females) were collected near the city of Corrientes, Province of Corrientes, Argentina (27°28'S - 58°50'W) between January 2001 and September 2004. A total of four nematode species in adult stage, Strongyloides sp., Oswaldocruzia sp., Cosmocerca podicipinus, Cosmocerca parva and two species in larval stage, Spiroxys sp. and Physaloptera sp. were recovered from the digestive tract, lungs and gastric mucosa. We present morphologic characters (some of them with scanning electron microscopy), metric information and range extensions for these nematode species. This is the first report of nematode parasites of P. albonotatus from Argentina.